Water tracking in surface water, groundwater and soils using free and alginate-chitosan encapsulated synthetic DNA tracers. (1st October 2020) - Pang, Liping; Abeysekera, Gayan; Hanning, Kyrin; Premaratne, Aruni; Robson, Beth; Abraham, Phillip; Sutton, Richard; Hanson, Carl; Hadfield, John; Heiligenthal, Laura; Stone, Dana; McBeth, Kurt; et al.
Highlights: 20 unique DNA tracers are available as free or microencapsulated molecules. Novel alginate-chitosan microencapsulated DNA tracers were developed. Encapsulated DNA tracers degraded less and were more negatively charged. Proof-of-concept studies showed promise in surface water, groundwater and soils. DNA tracers were directly detected at 1 km distance in a surface stream. ABSTRACT: Investigating contamination pathways and hydraulic connections in complex hydrological systems will benefit greatly from multi-tracer approaches. The use of non-toxic synthetic DNA tracers is promising, because unlimited numbers of tracers, each with a unique DNA identifier, could be used concurrently and detected at extremely low concentrations. This study aimed to develop multiple synthetic DNA tracers as free molecules and encapsulated within microparticles of biocompatible and biodegradable alginate and chitosan, and to validate their field utility in different systems. Experiments encompassing a wide range of conditions and flow rates (19 cm/day–39 km/day) were conducted in a stream, an alluvial gravel aquifer, a fine coastal sand aquifer, and in lysimeters containing undisturbed silt loam over gravels. The DNA tracers were identifiable in all field conditions investigated, and they were directly detectable in the stream at a distance of at least 1 km. The DNA tracers showed promise at tracking fast-flowing water in the stream, gravel aquifer and permeable soils, but were unsatisfactory at tracking slow-moving groundwater in the fine sand aquifer. In the surface water experiments, the microencapsulated DNA tracers' concentrations and mass recoveries were 1–3 orders of magnitude greater than those of the free DNA tracers, because encapsulation protected them from environmental stressors and they were more negatively charged. The opposite was observed in the gravel aquifer, probably due to microparticle filtration by the aquifer media. Although these new DNA tracers showed promise in proof-of-concept field validations, further work is needed before they can be used for large-scale investigations. Graphical abstract: Image, graphical abstract